Oikèma ou pièce polyvalente recherches sur une installation commerciale de l'Antiquité grecque - Karvonis, Paulos ca. 20./21. Jh (Acces archaeology, 2018)
This volume discusses the evolution of oikéma - the most common type of commercial facility in ancient Greece - through a study that covers a large area including Continental Greece, the Aegean islands, the Ionian islands and the west coast of Asia Minor